The Effect of Selected Physical Activities with Different Levels of Cognitive-Motor Interaction on Children's Executive Functions - Amine Lashkarizade; Vahid Roohollahi; Mahshid Zarezade; Amin Khodabakhshzade (University of Tehran, 2020)
Exercise and physical activity have positive effects on physical and mental performance, but their effect on cognitive function needs to be explained in more detail. This study examined the effect of selected physical activities with different levels of cognitive-motor interaction on the executive functions of 76 girls aged 10 to 12 years in Bam city, with mean and standard deviation of body mass index of 18.5 1 1.5 and average intelligence of 10.5 9 9.9. Based on the pre-test score, they were randomly divided into four groups (high cognitive-high motor, low cognitive-high motor, high cognitive-low motor and low cognitive-low motor). The results of covariance analysis showed that high cognitive-motor lifting exercises have a positive effect on attention and memory function of executive functions of 10 to 12-year-old girls and low cognitive-high-motor and low-cognitive-high-motor cognitive exercises have a positive effect on attentional and inhibitory components. There was a significant difference between high-motor, high-motor, low-motor, low-cognitive, high-motor, and low-cognitive-motor cognitive exercises in the attention component, but no significant difference was found in the component of working memory and inhibition. Therefore, based on the results of this research, by designing high-mobility cognitive exercises in the educational environment, it is possible to provide improvement of executive functions. Therefore, it is hoped that researchers will use the results of this research to improve the executive functions of children .